REVITALIZATION OF ISLAMIC EDUCATION: ADAPTIVE STRATEGIES IN FACING THE CURRENTS OF GLOBAL MODERNIZATION: REVITALISASI PENDIDIKAN ISLAM: STRATEGI ADAPTIF DALAM MENGHADAPI ARUS MODERNISASI GLOBAL - Moh. Hasan Mahayudin (STAI Ihyaul Ulum Gresik, 2025)
This Study discusses the efforts to revitalize Islamic education in response to the increasingly complex challenges of global modernization. Modernization, marked by technological advancement, cultural globalization, and shifting social values, demands that Islamic education systems adopt adaptive strategies without compromising their core Islamic values. Using a qualitative approach based on library research, this article outlines several adaptive strategies that can be implemented by Islamic educational institutions, including the reconstruction of an integrative curriculum, transformation of pedagogy through technology, strengthening the role of teachers and institutional leadership, as well as reorientation of Islamic educational values and vision. The findings reveal that Islamic education holds great potential to become a transformative force in shaping a generation of Muslims who are excellent, moderate, and competitive in the global era. This revitalization requires the support of all stakeholders, including the government, educational institutions, educators, and the wider community.